2006
DOI: 10.1016/j.tplants.2006.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the ESCRTing machinery in eukaryotes

Abstract: The profile of protein sorting into multivesicular bodies (MVBs) has risen recently with the identification of three heteromeric complexes known as ESCRT-I,-II,-III (Endosomal Sorting Complex Required for Transport). Genetic analyses in yeast have identified up to 15 soluble class E VPS (vacuolar protein sorting) proteins that have been assigned to the ESCRT machinery and function in cargo recognition and sorting, complex assembly, vesicle formation and dissociation. Despite their functional importance in yeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
203
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(207 citation statements)
references
References 69 publications
(121 reference statements)
3
203
1
Order By: Relevance
“…Interestingly, a comparative analysis of fully sequenced genomes revealed that components of the ESCRT machinery are highly conserved in yeast, mammals, plants (e.g. A. thaliana and Oryza sativa), Drosophila melanogaster and Caenorhabditis elegans (Winter and Hauser, 2006). Recently, the Arabidopsis homologue of the yeast Vps23 protein (Vps23p), which is a key component of ESCRT-I in yeast and animals, has been characterized (Spitzer et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a comparative analysis of fully sequenced genomes revealed that components of the ESCRT machinery are highly conserved in yeast, mammals, plants (e.g. A. thaliana and Oryza sativa), Drosophila melanogaster and Caenorhabditis elegans (Winter and Hauser, 2006). Recently, the Arabidopsis homologue of the yeast Vps23 protein (Vps23p), which is a key component of ESCRT-I in yeast and animals, has been characterized (Spitzer et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Endocytosis from the plate to ARA7-and ARA6-positive MVBs (Haas et al, 2007;Jaillais et al, 2008) was recently suggested as an alternative degradation pathway to remove monoubiquitinated proteins by the ESCRT machinery (Winter and Hauser, 2006). In favor of this hypothesis, an Arabidopsis mutant in one of the ESCRT-I components (elch) was reported that produces multinucleated cells in several cell types.…”
Section: Vesicle Trafficking Involved In Cell Plate Maturationmentioning
confidence: 99%
“…Plants also possess ESCRT proteins (Winter and Hauser, 2006;Schellmann and Pimpl, 2009;Shahriari et al, 2011), but there are no clear homologs to the ESCRT-0 complex (Leung et al, 2008), and the exact location of the other complexes is unclear. Nevertheless, several studies with mutated ESCRT proteins point to their presence at least at the LE.…”
Section: Introductionmentioning
confidence: 99%